THE PRACTICAL NECESSITY OF EUROBONDS IN THE FINANCIAL MARKET OF UZBEKISTAN AND THEIR IMPACT ON THE ECONOMY - Aziza Davlatyorova (Galaxy International Interdisciplinary Research Journal, 2023)
This article describes the activities of Uzbekistan in the world and domestic financial markets, international securities market and stock exchanges.